REFLEKSI METAFISIK PADA SIMBOL MAJANG DAN TARUB DALAM UPACARA PERKAWINAN ADAT JAWA (GAYA JOGJAKARTA) - Dewi Rochani (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2009)
AbstractJavanese always makes symbols that reflect their philosophyof life. One of them is in their wedding ceremony, especially“Majang” and “Tarub”. The “Majang” and “Tarub”, which is such wedding materials, symbolize expectations of Javanese familyto bride and groom in order to get happiness and peaceful life, and messages/ advices to the audience. The Javanese have insights that the quantity of reality tends to be monism. The quality of reality tends to be spiritualism but it still gives us a room to think rationally and pragmatically. The dynamic of reality tends to be idealism without ignoring the realism of life. The ontology norm of Javanese shows a harmony with surroundings, natural and supernatural life.Keyword: majang, tarub, monism, spiritualism, idealism, fatalism, harmony, ritual.